THE STRENGTH OF THE CONNECTION PARTS WITH GUARANTEED STRETCH, RECOVERED THE BALL FLOOR - Artemchuk, V. V. (Science and Transport Progress, 2008)
The article deals with description of the results of experimental studies of strength of joints with guaranteed tightness for details restored with electrolytic layered coatings by means of programmed electrolysis. The comparative analysis of restored layer structure and strength of stationary joint, which samples were restored according to the technology developed, with the samples restored with direct current and the ones not restored at all is conducted.